DAMPAK KEKERASAN DALAM RUMAH TANGGA TERHADAP TINGKAT PERAWATAN DIRI - Eka Purwati; H Herniyatun; Diah Astutiningrum (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2015)
Data of national commission of women (2005) in 2005 shows that there has been 455 cases of domestic violence, domestic violence is either physical or non physical, done actively or in a passive way (not done), desired by the perpetrator, and no adverse effect on the victim (physical or psychological). The effect can be seen from the daily victims of domestic violence. Self care is one of daily activities of the victim. There are various reasons for the lack of self care physical fatigue and loss of consciousness.The study is aimed to determine the influence of domestic violence on the level self care. This is a non experimental study using cross sectional approach. The samples consist of 30 respondents. The data analysis technique is Chi Square.Analysis of the data indicated a significant count of p=1.000 physical abuse, p=1.000 psychical abuse, p=1.000 economic abuse, p=1.000 sexual abuse. p > 0.05 means that there is no significant effect among the physical, emotional, economic, and sexual domestic violence with the level of self care. While the results of p count of domestic violence with self care show p 1.000 or p > 0,05. Keywords: Domestic Violence, Self Care.